Study on Biodegradable Random Copolyesters Derived From 1,4-Butane Diol, Terephthalic Acid and Adipic Acid/Sebacic Acid - Jaisankar, V.; Nanthini, R.; Karunanidhi, M.; Ravi, A. (Asian Journal of Chemistry, 2010)
A series of high molecular weight polyesters, poly(butylene adipate-co-butylene terephthalate)(PBAT) and poly(butylene sebacate-co-butylene terephthalate) (PBSeT) were synthesized by a direct melt polycondensation method using titanium tetraisopropoxide (TTiPO) as catalyst. The structure, average molecular weights and physical properties of the resulting random copolyesters were analyzed by IR, differential scanning calorimetry and X-ray diffraction studies. The effect of copolymer composition on the physical and thermal properties, as well as enzymatic degradation was investigated. The enzymatic degradation was performed in a buffer solution with enzyme cylindracea lipase. The rate of enzymatic degradation of these polyesters were compared. The poly(butylene adipate-co-butylene terephthalate) has highest enzymatic degradation rate than poly(butylene sebacate-co-butylene terephthalate). It appears that the key factor affecting material degradation was its crystallinity.